Periocular Cutaneous Mucormycosis Caused by Saksenaea erythrospora - Putthirangsiwong, Bunyada; Mahaisavariya, Pornchai; Chokthaweesak, Weerawan; Selva, Dinesh (Journal of Pediatric Infectious Diseases, 2019)
Saksenaea erythrospora is a rare pathogen in humans. Ten adult cases have been previously reported, eight manifested with cutaneous infection, and two presented with invasive rhinosinusitis infection. The authors present a 16-month-old boy with progressive painful mass at the right medial canthus and upper cheek that was unresponsive to broad-spectrum antibiotics. He underwent an anterior orbitotomy and biopsy. Histopathology revealed broad nonseptate sterile hyphae and grew S. erythrospora, which was confirmed by molecular techniques. The patient was treated with intravenous liposomal amphotericin B and oral itraconazole combined with aggressive surgical debridement. The patient made a complete recovery without long-term complications at 4 months of follow-up. Primary cutaneous mucormycosis caused by S. erythrospora may rarely involve the periocular region and mimic chronic dacryocystitis. We report the first case of pediatric periocular cutaneous mucormycosis caused by S. erythrospora.
Keywords: cutaneous mucormycosis; dacryocystis; Saksenaea erythrospora; liposomal amphotericin B